Social entrepreneurship: “From the Sky to the Earth” – Malaysia’s experience - Yohan Kurniawan; Farok Zakaria; Nur Azuki Yusuff; Wan Mohamad Wan Abdullah (2011)
Social Entrepreneurship (SE) is a program that integrates theory with its application in society. In practice, the SE program aims to teach about the culture of a society in a country. It also gives an understanding to participants about the business carried out by the community. Besides that, the program also allows participants to explore new business opportunities or improve existing business by creating business network between them, both at national and international levels. As mentioned earlier, the SE program essentially is a program that aims to realize the knowledge and theory (“from sky”) into real life (“to earth”). This is not something which is easy to implement. There are various challenges and obstacles in this field. This paper describes the experience gained from social entrepreneurship program in Malaysia which was conducted by Universiti Malaysia Kelantan (UMK). This program is called Social Entrepreneurship of Economy Development (SEED). This program is a voluntary programme which supports the fifth thrust of UMK’s Strategic area, and Kelantan is a land that has a unique culture and way of life in comparison to other regions in Malaysia. The uniqueness of this program is it differs from similar programs held in other countries such as Indonesia and Vietnam. In this course, students will be given the chance to apply what they have learned in their respective courses into the real world. SEED had been implemented in seven villages in the district of Tumpat. These villages are Tujuh (product: free range Chicken), Tujuh Masjid (product: cattle and goat), Belukar Neting (product: noni Juice), Pak Kerau Hilir (product: catfish), Pak Kerau Hulu (product: Akok and Batek), Sungai Tapang (product: Mushroom), and Tujuh Tengah/ Pos Banjar (product: chillies). In this programme, 18 international participants from Switzerland, Singapore, Brunei, Thailand, Vietnam, and 49 UMK students had diligently taken part in developing the business plan for various projects. There were seven projects altogether and after the program started, follow-up supervision was conducted to determine the level of development of the business plan drawn up during the SE program. From the seven programmes, four programmes failed, two programmes were stable, and one programme was successful. Through this paper, we would like to share experiences on social entrepreneurship in Malaysia, especially in Kelantan. There have been many challenges faced by this program. Some of these challenges are the absence of follow-up activities for the program, the difficulty in upholding students' motivation, students' lack of knowledge and skills, minimum involvement of experts in this program, cultural differences between participants, villagers’ motivation, and problems with the program facilitators.